2005
DOI: 10.1063/1.2133910
|View full text |Cite
|
Sign up to set email alerts
|

Second- and third-harmonic generation in birefringent photonic crystals and microcavities based on anisotropic porous silicon

Abstract: One-dimensional anisotropic photonic crystals and microcavities based on birefringent porous silicon are fabricated. The reflectance spectra demonstrate the presence of photonic band gap and microcavity modes with spectral positions tunable upon the sample azimuthal rotation around its normal and/or rotation of polarization plane of incident light. Simultaneous enhancement of second- and third-harmonic generation at the photonic band-gap edge due to the phase matching is observed. The angular positions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Second-and third-harmonic generation in birefringent PSi single layer and photonic crystals has been proposed [181][182][183]. Photonic structures can also be built laterally.…”
Section: Passive Photonic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Second-and third-harmonic generation in birefringent PSi single layer and photonic crystals has been proposed [181][182][183]. Photonic structures can also be built laterally.…”
Section: Passive Photonic Structuresmentioning
confidence: 99%
“…Using the high sensitivity of the resonance of a PSi microcavity, a switching function becomes available by monitoring the transmission or reflection of light at the resonance wavelength of the cavity. Second-and third-harmonic generation in birefringent PSi single layer and photonic crystals has been proposed [181][182][183]. The study of nonlinearities in PSi (porosity up to 70%) optical waveguides at 1550 nm showed that two-photon absorption and self-phase modulation coefficients are comparable to those of bulk Si, whereas free-carrier absorption and dispersion are significantly faster and stronger in PSi [206].…”
Section: Passive Photonic Structuresmentioning
confidence: 99%
“…The adjustment of the formation process of por-Si MLS offers possibilities to prepare high-quality optical mirrors with desirable reflection and dispersion. [2] Raman scattering, [3,4] secondand third-harmonic generations, [5,6] and photonic crystal properties [2,7,8] of porSi are well explored and these data show the possibilities of tailoring the optical and nonlinear optical properties of Si-based nanocomposites. MLSs based on por-Si can be considered as one-dimensional photonic crystals to control a light stream inside a chip and the radiative processes within the photonic bandgap (PBG) or in the area of microresonator modes.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to such well known effects as slow light, i.e., a substantial decrease of the light group velocity [3], spatial and spectral light localization [4], the decrease of the optical excitation threshold of PhC based laser structures [5,6]. An important property of photonic crystals is also a manifold amplification of the efficiency of the nonlinear-optical effects such as harmonics' generation [7,8] and nonlinear magneto-optical effects [9]. When the nonlinear interaction of the pulsed laser radiation with the PhC structure is sufficient, the so-called gap solitons can exist within the photonic crystals [10,11].…”
Section: Introductionmentioning
confidence: 99%